The clinical significance of thrombocytopenia in sepsis and septic shock: a systematic review and meta-analysis - Basel F. Alqeeq; Mohammed Ayyad; Maram Albandak; Waseem J. Almadhoun; Mahmoud Kullab; Ahmed W. Ghabayen; Mohammed Al-Tawil (BMC Anesthesiology)
Abstract Background Thrombocytopenia (TCP) is a common finding in critically ill patients that has been linked to a worse prognosis. Specifically, sepsis is a major risk factor for TCP. Several observational studies have examined the prognostic role of TCP and its correlation with clinical outcomes in patients with sepsis. Methods We conducted a systematic search through Medline, Scopus and CENTRAL, from inception until June 2024, in order to identify studies that discussed the effects of TCP on clinical outcomes in patients with sepsis or septic shock. This review was performed in accordance with the Meta-Analysis of Observational Studies in Epidemiology (MOOSE) guidelines. Study endpoints were ICU mortality, 28-day mortality, major bleeding and mechanical ventilation. Results We included twelve studies enrolling 14,093 patients in this meta-analysis. TCP was diagnosed at intensive care unit (ICU) admission in 5481 (39%) patients; on the other hand, it was encountered during the course of ICU stay in 1474 (10%) cases. Patients with TCP had significantly higher risks of ICU mortality (Odds Ratio: 1.93, 95% CI [1.6–2.33]; p < 0.01). and 28-day mortality (odds ratio: 1.98, 95% CI [1.67, 2.35]; p < 0.00001). Furthermore, patients with severe TCP (platelet count < 50 * 109/L) had even higher odds of ICU mortality (odds ratio: 3.38, 95% CI [2.25, 5.08]; p < 0.00001). Major bleeding events were significantly more frequent in patients with TCP (odds ratio: 3.26, 95% CI [2.26, 4.72]; p < 0.01). Conclusion TCP exhibits significant clinical implications in critically ill patients admitted with sepsis and is associated with enhanced mortality and worse clinical outcomes. Nonetheless, this meta-analysis quantifies the significant association between TCP and poor clinical outcomes in patients with sepsis and septic shock.